Introducing Dayak Culture for Elementary School Students through Huma Betang Philosophical Poems - Diplan Diplan; Misnawati Misnawati; Wahidin Wahidin; Widya Permata Dilla; Wahyu Nugroho; Siti Patimah; Alimuddin A Djawat; Aam Rifaldi Khunaifi; Ade Salahudin Permadi; Anwarsani Anwarsani; Nabila Salwa (International Journal of Educational Evaluation and Policy Analysis, 2025)
Dayak culture offers a wealth of noble values that can positively shape the character of elementary school students. This paper aims to: (1) identify the values of Dayak culture contained in the poem "Philosophy of Huma Betang". (2) Explain the method of introducing these cultural values to elementary school students. (3) Describe the effectiveness of using poetry as a medium of cultural introduction. One of the effective methods to introduce Dayak culture to students is through poetry. This article discusses the poem "Philosophy of Huma Betang" by Misnawati as a medium that conveys cultural values in an interesting and easy-to-understand manner for elementary school students. The importance of this research is based on the need to understand and preserve Dayak cultural values. This research uses a descriptive qualitative approach, by identifying the cultural values contained in the poem. The method of introducing cultural values to elementary school students involves reading with expression, discussion, creative activities, and educational visits. The results of the study show that the use of the poem "Philosophy of Huma Betang" is successful in increasing students' understanding and appreciation of Dayak culture. Students show high interest, they can remember well the values learned, and show improvement in language skills and creativity. Educators also give positive feedback on the effectiveness of this method in learning in elementary school classrooms.